2015
DOI: 10.1098/rstb.2014.0346
|View full text |Cite
|
Sign up to set email alerts
|

Percussive technology in human evolution: an introduction to a comparative approach in fossil and living primates

Abstract: Percussive technology is part of the behavioural suite of several fossil and living primates. Stone Age ancestors used lithic artefacts in pounding activities, which could have been most important in the earliest stages of stone working. This has relevant evolutionary implications, as other primates such as chimpanzees and some monkeys use stone hammer-and-anvil combinations to crack hard-shelled foodstuffs. Parallels between primate percussive technologies and early archaeological sites need to be further exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 45 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Until recently, our understanding of technological behaviours of the earliest hominins revolved around the intentional production of sharp-edged flakes used as cutting tools [10]. The past decade has shown that percussive behaviours also played an important role in hominin subsistence strategies [11][12][13][14][15][16][17]. The new field of primate archaeology [18] has highlighted the potential for developing a greater understanding of hominin percussive technology through the study of modern primate percussive tools.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, our understanding of technological behaviours of the earliest hominins revolved around the intentional production of sharp-edged flakes used as cutting tools [10]. The past decade has shown that percussive behaviours also played an important role in hominin subsistence strategies [11][12][13][14][15][16][17]. The new field of primate archaeology [18] has highlighted the potential for developing a greater understanding of hominin percussive technology through the study of modern primate percussive tools.…”
Section: Introductionmentioning
confidence: 99%
“…Stone tool percussion is of increasing interest to primatology, archaeology and primate archaeology [ 1 ]. The durable nature of lithic artefacts makes them the prime candidate for tracing the development of primate and hominin percussive technologies through time [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the experiments, we used the same type of quartz and reproduced similar marks to those described at similar sites (Crabtree, ; Shott, ; Leakey and Roe, ; Curtoni, ; Mourre and Jarry, ; Barsky et al ., ; Hayden, ; de la Torre and Hirata, ; Li, ; Rodríguez‐Álvarez, ; Li et al ., ). Geological data indicate that the pebble layer was a possible source of raw material for hominins.…”
Section: Tests On Anvilsmentioning
confidence: 99%